Damage Mechanics Experimental Background - Basista, M. (Engineering Transactions, 1988)
The present paper is a synthetic review of available experimental results, concerning damage nucleation and growth in various materials at diverse loading conditions. An emphasis is placed on the physical complexity of the damage processes. To this end, an inference of the state of stress, type of applied load, material mesostructure and temperature are studied in detail. Characteristic features attributed to the damage process, such as damage-induced material inelasticity and anisotropy are stressed. The second part of the review will be devoted to selected damage models published so far.